Familial Hypercholesterolemia in Children. The Current State of the Problem - Dinara I. Sadykova; Karina R. Salakhova; Liliya F. Galimova; Eugeniya S. Slastnikova; Chulpan D. Khaliullina ("Paediatrician" Publishers LLC, 2023)
Cardiovascular diseases are the leading cause of disability and mortality worldwide. Cardiovascular mortality rate is steadily increasing despite the large-scale preventive measures. Familial hypercholesterolemia is the most common genetically determined disorder of lipid metabolism as the major cause of blood circulatory system diseases development and progression. Worldwide, there are 6.8-8.5 million children with this primary dyslipidemia. Early (in childhood) diagnosis of familial hypercholesterolemia is crucial for the timely initiation of lipid-lowering therapy in order to reduce the atherosclerosis progression and the risk of life-threatening cardiovascular events. New screening programs have been implemented, new biomarkers of the disease have been studied, and lipid-lowering drugs with new mechanisms of hypolipidemic action have been developed to increase the efficacy of these activities in economically developed countries.